2021
DOI: 10.4103/ijmr.ijmr_768_21
|View full text |Cite
|
Sign up to set email alerts
|

One Health aspects & priority roadmap for fungal diseases

Abstract: Fungal diseases have not been taken seriously in public health agendas as well as research priorities, despite of globally causing an estimated two million deaths every year, and the emergence of many troublesome fungal pathogens like Candida auris, azole resistant Aspergillus fumigatus, terbinafine and azole resistant dermatophytes, and zoonotic sporotrichosis in humans. Fungi are also responsible for huge losses of agricultural products and stored crops as well as recent massive and unexpected mortality in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Though we didn't find any case with post transplant, haematological malignancies, post-pulmonary tuberculosis in our study. Nevertheless, these are found as potential risk factors in published literature on mucormycosis; hence there is a strong association of co-morbidities and fungalcoinfection (5,8,9,21). History of corticosteroid intake for the treatment of COVID-19 was present in 76.3 -88% of cases in several studies (10,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though we didn't find any case with post transplant, haematological malignancies, post-pulmonary tuberculosis in our study. Nevertheless, these are found as potential risk factors in published literature on mucormycosis; hence there is a strong association of co-morbidities and fungalcoinfection (5,8,9,21). History of corticosteroid intake for the treatment of COVID-19 was present in 76.3 -88% of cases in several studies (10,24).…”
Section: Discussionmentioning
confidence: 99%
“…(4,5,6,7). Emerging fungal infections is a growing concern worldwide, more so in India due to temperature adaptation, under-diagnosis, millions of diabetics and poor awareness (5,8,9). Globally, the prevalence of mucormycosis varied from 0.005 to 1.7 per million populations, while it is nearly 80 times higher (0.14 per 1000) in India (10).…”
Section: Introductionmentioning
confidence: 99%
“…About 1 billion people in the world are thought to suffer from a fungal infection, an increase due to host factors as well as new mechanisms of virulence or resistance. Additionally, recent environmental and epidemiological evidence of endemic mycoses shows changes in the geographic prevalence of pathogenic fungi worldwide [ 327 , 328 ]. It has recently been suggested that invasive mycoses are undergoing etiopathogenic changes that are making these diseases even more prevalent, and that the geographical distribution is moving towards geographical areas where it did not exist before [ 329 ].…”
Section: Clinical Use Of Polyenesmentioning
confidence: 99%
“…Nearly 6 million different species of fungi exist, and about 600 of them can cause human disease. Fungal diseases represent a health concern, because of high mortality rates and constant problems with antifungal resistance . There are no licensed vaccines to prevent fungal diseases.…”
Section: The Need For New Antifungalsmentioning
confidence: 99%